2019
DOI: 10.1212/con.0000000000000699
|View full text |Cite
|
Sign up to set email alerts
|

Primary Progressive Aphasias and Apraxia of Speech

Abstract: PURPOSE OF REVIEW: This article reviews two of the primary progressive aphasias (PPAs), disorders characterized by the early and predominant impairment of language, and primary progressive apraxia of speech, a degenerative motor speech disorder that is closely related to PPA. An outline of the history and controversy surrounding how these disorders are classified is provided before the article focuses on each disorder's clinical and imaging features. RECENT FINDINGS: Over the past decade, the classification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 37 publications
(77 reference statements)
2
48
0
2
Order By: Relevance
“…The anterior components of the language network, including the inferior frontal lobe, and the anterior opercular and perisylvian areas, including the anterior insula and superior temporal gyrus, have been implicated as the neuroanatomical substrates of nfvPPA ( 14 ). The lesions identified in our case correspond to these areas and may therefore account for the observed language impairments, including generalized auditory agnosia, which is seldom observed in typical nfvPPA.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior components of the language network, including the inferior frontal lobe, and the anterior opercular and perisylvian areas, including the anterior insula and superior temporal gyrus, have been implicated as the neuroanatomical substrates of nfvPPA ( 14 ). The lesions identified in our case correspond to these areas and may therefore account for the observed language impairments, including generalized auditory agnosia, which is seldom observed in typical nfvPPA.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some controversies, three clinical variants of primary progressive aphasia (PPA) are generally recognised: the non‐fluent/agrammatic variant (nfvPPA or avPPA), in which there may or may not also be an apraxia of speech (AOS); the semantic variant (svPPA), and the logopenic variant (lvPPA) 1,2 . While nfvPPA and svPPA are characterised as linguistic variants of frontotemporal dementia (FTD), 3 lvPPA is most often associated with Alzheimer‐type pathology and is therefore classified with Alzheimer's disease (AD) 4 .…”
Section: Ppa Variant Nonfluent/agrammatic (Nfvppa Avppa) Semantic (Smentioning
confidence: 99%
“…Primary progressive apraxia of speech (PPAOS) is a neurodegenerative syndrome characterized by progressive and initially isolated (or predominant) AOS (Duffy 2006, Josephs et al 2012. Although the classification of PPAOS as a distinct disorder from the non-fluent variant of primary progressive aphasia (nfvPPA) was suggested more than a decade ago, its application and definition remain variable (Botha and Josephs 2019). Indeed, some authors have suggested that PPAOS includes all patients with AOS as the predominant symptom (Harris et al 2013, Josephs et al 2010, 2013, Josephs et al 2006, Mesulam 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The distinction of patients with predominant AOS (isolated or not) from those with nfvPPA is motivated by recent studies suggesting differences in the underlying neurophysiology (Utianski et al 2019) and pathology, neuroimaging abnormalities (Josephs et al 2013), clinical manifestations (Josephs et al 2013), and disease progression (Whitwell et al 2017). Further, it has important implications for clinical management (Botha and Josephs 2019, Josephs et al 2013. Comparably, the need to further categorize patients with PAOS into PPAOS or DAOS subcategories is motivated not only by the presence of agrammatism but also by possible differences similar to what is observed between PAOS and nfvPPA (i.e., neuroimaging, clinical manifestations, disease progression, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation